Exchange rate sensitivity of China's bilateral trade flows - Jiao Wang; Andy G. Ji (Bank of Finland, Institute for Economies in Transition (BOFIT), 2006)
Traditional assessments of the impact of exchange rate depreciation or appreciation on trade have involved estimating the elasticity of trade volume to relative prices.Such studies relied heavily on aggregated trade data.More recent studies employ bilateral trade data and methodologies such as ECM and gravity models.This study uses a generalized gravity model with data panel analysis in assessing the impact of currency depreciation or appreciation on bilateral trade flows between China and its top trading partners. The empirical evidence suggests exchange rates (both real and nominal) do not exert a significant influence on the overall exports from China.Thus, a devaluation or revaluation of the yuan should be expected to have only limited impact on China's trade balance.Moreover, previous studies provide limited evidence of a negative relation between exchange rate volatility and trade flows. Given the current revaluation expectations, we find China's anticipated shift toward a more flexible exchange rate regime fails to address China's trade surplus issues, and thus will merely lead to a revaluation of the nominal exchange rate and increased exchange rate volatility.It appears a major overhaul of the country's heavily subsidized export regime must first occur for the exchange rate to assume a larger role in China's international trade.
URN:NBN:fi:bof-201408072037
Keywords: C22; C23; F14; F31; 330; Exchange Rate; Trade; China; Competition; Gravity Model; Panel